2012
DOI: 10.1007/s10856-012-4776-2
|View full text |Cite
|
Sign up to set email alerts
|

Strategies towards injectable, load-bearing materials for the intervertebral disc: a review and outlook

Abstract: Currently available treatments for the degenerated intervertebral disc present disadvantages, such as surgical invasiveness and inadequate load distribution results. Load-bearing, injectable materials may be interesting for future therapies, but have not been studied in depth.In this study, the existing literature was screened for studies on injectable materials for the intervertebral disc and a rationale for load-bearing, injectable materials was formulated.Requirements for such a material were discussed, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Several systematic studies have been conducted to evaluate the radiopacity of injectable CPCs. These studies have emphasized the importance of investigating the radiopacity of injectable bone cement [ 254 , 255 , 256 , 257 ]. In addition to radiopacity, other properties such as mechanical properties, degradation profile, and porosity are important parameters to study in CPC composites [ 258 ].…”
Section: General Principles Of Bone Substitute Synthesismentioning
confidence: 99%
“…Several systematic studies have been conducted to evaluate the radiopacity of injectable CPCs. These studies have emphasized the importance of investigating the radiopacity of injectable bone cement [ 254 , 255 , 256 , 257 ]. In addition to radiopacity, other properties such as mechanical properties, degradation profile, and porosity are important parameters to study in CPC composites [ 258 ].…”
Section: General Principles Of Bone Substitute Synthesismentioning
confidence: 99%
“…A frequency of 5 Hz was used and the maximum stress level was set to 13 MPa, based on preliminary testing, and similar to what has previously been used for a calcium sulphate and phosphate-based bone cement [ 9 ]. This stress level is also in the range of reported compressive strengths of human trabecular bone (1–23 MPa) [ 37 39 ], and higher than what has been suggested for fatigue testing of materials for spinal applications (5 MPa) [ 40 ]— one suggested use for ceramic cements in load-bearing applications is vertebroplasty [ 14 , 41 ]. The specimens were tested until catastrophic failure, i.e., until occurrence of a sudden drop in stress, or a run-out of 5 million cycles, as indicated by the standard for fatigue testing of acrylic bone cements [ 23 ].…”
Section: Methodsmentioning
confidence: 98%
“…Inorganic radiopaque agents such as barium sulfate, strontium carbonate, bismuth salicylate basic and zirconium dioxide are usually incorporated into CaP cements, yet this incorporation could cause changes in the physiochemical properties [ 45 , [79] , [80] , [81] ]. Overall, several systematic researches on radiopacity evaluation of injectable CPCs have been undertaken [ [82] , [83] , [84] , [85] ]. These studies highlighted the need for examining the radiopacity of an injectable bone cement.…”
Section: Properties Of Injectable Cap Bone Cementsmentioning
confidence: 99%
“…These studies highlighted the need for examining the radiopacity of an injectable bone cement. Overall it was concluded that the evaluation parameters for radiopacity should be similar with those of the clinical procedures which are 60–130 kV and 3.1–10 mAs [ 83 ].…”
Section: Properties Of Injectable Cap Bone Cementsmentioning
confidence: 99%